Killing Effects of an Isolated Serratia marcescens KH-001 on Diaphorina citri via Lowering the Endosymbiont Numbers - Hu, Wei; Kuang, Fan; Lu, Zhanjun; Zhang, Ning; Chen, Tingtao (Frontiers in Microbiology, 2018)
Huanglongbing (HLB) is the most devastating citrus disease worldwide, and suppression of the Asian citrus psyllid (Diaphorina citri) is regarded as an effective method to inhibit the spread of HLB. In this study, we isolated a strain named as Serratia marcescens KH-001 from D. citri nymphs suffering from disease, and evaluated its killing effect on D. citri via toxicity test and effect on microbial community in D. citri using high-throughput sequencing. Our results indicated that S. marcescens KH-001 could effectively kill 83% of D. citri nymphs, while the fermentation products of S. marcescens KH-001 only killed 40% of the D. citrinymphs. High-throughput sequencing results indicated that the S. marcescens KH-001 increased the OTU numbers from 62.5 (PBS buffer) to 81.5, while significantly lowered the shannon index compared with Escherichia coli DH5α (group E) (p<0.05).OTU analysis showed that the S. marcescens KH-001 had significantly reduced the relative abundance of endosymbionts Wolbachia, Profftella and Carsonella in group S compared with that in other groups (p<0.05). Therefore, the direct killing effect of the fermentation products of S .marcescens KH-001 and the indirect effect via reducing the numbers of endosymbionts (Wolbachia, Profftella and Carsonella) of D. citri endow S. marcescens KH-001 a sound killing effect on D. citri. Further work need to do before this strain is used as a sound biological control agents.